2016
DOI: 10.1371/journal.pone.0157681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pseudo-Haptic Interactions with Soft Objects in Virtual Environments

Abstract: This paper proposes a pseudo-haptic feedback method conveying simulated soft surface stiffness information through a visual interface. The method exploits a combination of two feedback techniques, namely visual feedback of soft surface deformation and control of the indenter avatar speed, to convey stiffness information of a simulated surface of a soft object in virtual environments. The proposed method was effective in distinguishing different sizes of virtual hard nodules integrated into the simulated soft b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…1) Displacement: The first approach visualizes the distorted displacement of user input D 0 (Fig. 2(a)) [29]- [34], [36]- [40], [88]. L ecuyer et al [29] asked users to push their thumb on a piston mounted on a passive spring, and they viewed the distorted thumb displacements D 0 on the display.…”
Section: Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…1) Displacement: The first approach visualizes the distorted displacement of user input D 0 (Fig. 2(a)) [29]- [34], [36]- [40], [88]. L ecuyer et al [29] asked users to push their thumb on a piston mounted on a passive spring, and they viewed the distorted thumb displacements D 0 on the display.…”
Section: Compliancementioning
confidence: 99%
“…Li et al [36], [38], [88] proposed a surgical training system that used pseudo-haptics for tumor identification during palpation. They proposed presenting the hardness of the tumor using pseudo-haptics on soft tissue surfaces.…”
Section: B Trainingmentioning
confidence: 99%
“…Haptic information can also be conveyed to a user during teleoperation tasks in the form of visual cues. This cross-modal sensation between visual and tactile sensing is usually termed pseudo-haptics (Li et al, 2016). In "Proposal and Evaluation of Visual Haptics for Manipulation of Remote Machine System" by Haruna et al, this approach is assessed using electroencephalogram (EEG) data on a Virtual Reality (VR) setting.…”
Section: Contents Of the Research Topicmentioning
confidence: 99%
“…The results suggest that applying a high CD gain can help reduce task completion time [9,10]. In the context of kinesthetic interactions, some studies suggested that the visual feedback provided by different CD gains can influence kinesthetic perception and sometimes even override the perception available through force feedback [11][12][13]. Further, while using a force-feedback device, applying a large CD gain leads to a mismatch between hand motions and HIP motions, which thus could potentially influence the user's control of the HIP.…”
Section: Introductionmentioning
confidence: 99%